2016
DOI: 10.1080/17429145.2016.1148204
|View full text |Cite
|
Sign up to set email alerts
|

Differential physiological and antioxidative responses to drought stress and recovery among four contrasting Argania spinosa ecotypes

Abstract: Our study was undertaken to ascertain whether the change of the water status and the activation of superoxide dismutase and their isoenzymes in Argan tree can support edaphic drought tolerance and its recovery under rehydration. An experiment was conducted on four contrasting ecotypes of Argania spinosa plants: two contrasting coastal ecotypes (Admine (Adm) and Rabia (Rab)) and two contrasting inland ecotypes (Aoulouz (Alz) and Lakhssas (Lks)). Drought stress significantly decreased the leaf water potential an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 52 publications
3
21
0
Order By: Relevance
“…Drought stress is one of the most unfavorable environmental stress factors and can severely reduce crop yield and quality [1,2]. Drought stress can interfere with numerous physiological processes, including oxidative stress [3], membrane integrity [4], and enzyme activity [5], all of which could lead to plant growth inhibition.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Drought stress is one of the most unfavorable environmental stress factors and can severely reduce crop yield and quality [1,2]. Drought stress can interfere with numerous physiological processes, including oxidative stress [3], membrane integrity [4], and enzyme activity [5], all of which could lead to plant growth inhibition.…”
Section: Introductionmentioning
confidence: 99%
“…It has been extensively reported that drought stress induces reactive oxygen species (ROS) accumulation. Excessive ROS results in oxidative damage to cell structures, cell metabolism, and macromolecules, such as membrane lipids, nucleic acids, and proteins [1,10]. Thus, in order to keep the balance between and GOGAT are also related to drought stress response and they are often regarded as important metabolic indicators of drought tolerance [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…There are comparatively few studies that investigate the photosynthetic and stomatal responses of the argan tree to drought. Previous studies have indicated differences in the leaf water potential, antioxidant activity ( Diaz-Barradas et al, 2010 ; Chakhchar et al, 2015 , 2016 ), leaf morphology ( Diaz Barradas et al, 2013 ; Chakhchar et al, 2015 ) and chlorophyll fluorescence parameters ( Diaz-Barradas et al, 2010 ) response to drought of argan trees collected from different habitats. Despite the restricted range of the argan tree (950,000 ha: Lefhaili, 2010 ), genetic analyses have indicated variation between accessions collected from different habitats (hereafter referred to as ecotypes; El Bahloul et al, 2014 ) that may underpin this variety of response to water deficit.…”
Section: Introductionmentioning
confidence: 99%
“…However, the stomatal response to increased leaf to air VPD depends upon the adaptation of a plant to the prevailing growth conditions, with plants grown under conditions of high evapotranspirative demand exhibiting greater stomatal sensitivity to VPD ( Bauerle et al, 2004 ). Comparison of argan ecotypes under common garden conditions suggested that ecotypes from more arid habitats exhibited greater foliar levels of anti-oxidant activity and lower water potential values than their counterparts from regions with higher levels of rainfall ( Chakhchar et al, 2015 , 2016 ). It may therefore be expected that ecotypes from diverse habitats possess contrasting photosynthetic and stomatal responses to drought associated with underlying genetic variation.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, SOD reduces the risk of the formation of a more reactive hydroxyl radical (Meloni et al, 2003, Gill andTuteja, 2010). Chakhchar et al (2016) state that this enzyme has a crucial role in the survival of plants in stressful conditions. The significance of this enzyme is also shown by the fact that an excessive expression of SOD in transgenic tobacco plants showed tolerance to multiple stresses, such as drought and salinity (Badawi et al, 2004).…”
Section: Determination Of Antioxidant Enzymes Activitymentioning
confidence: 99%